Struktur Kepemilikan Saham terhadap Profitabilitas dan Nilai pada Perusahaan Perbankan - Surayya Surayya; Juliana Kadang (STIE Perbanas Surabaya, 2020)
This study aims to determine the effect of managerial and public ownership structures on profitability at the Foreign Exchange National Private Commercial Banks (BUSN), determine the effect of managerial and public ownership structures on firm value at Foreign Exchange National Private Commercial Banks (BUSN), and determine the effect of profitability on firm value in Foreign Exchange National Private Commercial Banks (BUSN). This research method uses descriptive quantitative as a type of research. The population is 35 banking companies, while the sample is 17 banking companies whose financial statements are listed on the Indonesia Stock Exchange. The date were collected through secondary data in the form of documents, namely financial reports for 2016 - 2018. The data analysis technique uses multiple regression analysis. The results showed that there was no influence of managerial share ownership structure on profitability and firm value. Furthermore, there is a significant effect of public share ownership structure on profitability while firm value has no significant effect. The implication is that managerial roles and participation are needed in this case the share ownership structure in order to increase the profitability and value of banking companies such as other companies listed on the Indonesia Stock Exchange.